86.6k views
5 votes
Is a solution to the equation 2(x - 5) = 9 - 3x + 7.


User Nyasia
by
5.5k points

2 Answers

4 votes
2x-10=9-3x+7
2x-10+10=9-3x+7-10
2x=9-3x+7-10
2x+3x= 9+7-10
5x=16-10
5x=6
X=6/5
User AShah
by
4.7k points
0 votes

Answer:

x=26/5

Explanation:

2(x - 5) = 9 - 3x + 7.

2x-10=9-3x+7

+3x +3x

5x+-10=16

+10=+10

5x=26

divide by 5x

x=26/5

User Lostsoul
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.